Diboranyl Phosphonium Cations: Synthesis and Chemical Properties. Issue 31 (8th October 2015) - Litters, Sebastian; Ganschow, Michael; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract: Hydride abstraction from the diborane [HB(hpp)]2 (hpp = 1, 3, 4, 6, 7, 8‐hexahydro‐2 H ‐pyrimido[1, 2‐ a ]pyrimidinate) followed by base stabilization led to the first (highly water sensitive) diboranyl phosphonium cations of the general formulas [HB(hpp)2 BPR3 ] + and [HB(hpp)2 BPHR2 ] + . The B–P bond strength could be varied over a relatively large range by choice of the substituents R on the phosphine. The cation [HB(hpp)2 BPCy3 ] + (Cy = cyclohexyl) was structurally characterized. The PCy3 base of this cation could be substituted by a stronger base (a carbene or a bicyclic guanidine). In solution, [HB(hpp)2 BPCy3 ] + very slowly decomposes, and [HB(hpp)3 BH] + was identified as one of the decomposition products. Abstract : Hydride abstraction from a diborane by B(C6 F5 )3 followed by addition of a phosphine yielded the first diboranyl phosphonium cations.